Sonification of Animal Tracks as an Alternative Representation of Multi-Dimensional Data: A Northern Elephant Seal Example - Duarte, Carlos M.; Riker, Paul; Srinivasan, Madhusudhanan; Robinson, Patrick W.; Gallo-Reynoso, Juan P.; Costa, Daniel P. (Frontiers in Marine Science, 2018)
Understanding movement of marine megafauna across the ocean is largely based on approaches and models based on analysis of tracks of single animals. While this has led to major progress, the possibility of concerted group dynamics has not been sufficiently examined, possibly due to challenges in exploring massive amounts of data required to this end. Here we report a sonification experiment, where the collective movement of northern elephant seals (Mirounga angustirostris) was explored by coding their group dynamics into sound. Specifically, we converted into sound data derived from a tagging program involving a total of 321 tagged animals tracked over a decade, between 20 February 2004 and 30 May 2014, consisting of an observation period of 90063 hours, composed of 1,027,839 individual positions. The data parameters used to provide the sound are position (longitude) and spread (degree of displacement taken for the active group). These data parameters are mapped to the sonic parameters of frequency (pitch) and amplitude (volume), respectively. Examination of the resulting sound revealed features of motion that translate into specific patterns in space. The serial departure of elephant seals to initiate their trips into waves is clearly reflected in the addition of tonalities, with coherent swimming of the animals conforming a wave reflected in the modulated fluctuations in volume, suggesting coordinated fluctuations in dispersion of the wave. Smooth changes in volume, coordinated with pitch variability, indicate that the animals spread out as they move further away from the colony, with one or a few animals exploring an ocean area away from that explored by the core wave. The shift in volume and pitch also signals at group coordination in initiating the return home. Coordinated initiation of the return to the colony is also clearly revealed by the sonification, as reflected in an increase in volume and pitch of the notes denoting the movement of each animal in a migration wave. This sonification reveals clear patterns of covariation in movement data, which drivers and triggers, whether intrinsic or environental, cannot be elucidated here but allow to formulate a number of non-trivial questions on the synchronized nature of group